Migrating and Settling in a Mobile World: Albanian Migrants and Their Children in Europe - Vathi, Zana (Springer, 2015)
This book draws on award-winning cross-generational research comparing the complex and life-changing processes of settlement among Albanian migrants and their adolescent children in three European cities: London (UK), Thessaloniki (Greece), and Florence (Italy). Building on key concepts from the social sciences and migration studies, such as identity, integration and transnationalism, the author links these with emerging theoretical notions, such as mobility, translocality and cosmopolitanism. Ethnic identities, transnational ties and integration pathways of the youngsters and adults are compared, focusing on intergenerational transmission in particular and recognizing mobility as an inherent characteristic of contemporary lives.